Ratio of All Unit Weight (AUW) to Thrust force of Upper Wing Aeromodelling Aircraft - Zuhdi, Muhammad; Doyan, Aris; Syahrial, Syahrial; Rokhmat, Joni; Kosim, Kosim (AMPLITUDO : Journal of Science and Technology Innovation, 2023)
The aircraft used in this study is the upper wing type which has the advantage of flight stability. This upper wing aircraft was designed by the researchers themselves with three different types of wings with a wing span of 1.35m and a fuse lag of 0.925 meters. There are four main forces that work when the plane is in the air, namely lift, thrust, air resistance and gravity. From the results of this study, it can be concluded that the heavier the aircraft unit being flown, the greater the minimum thrust required to fly the aircraft. The measurement results of the 3 aircraft weights, namely 917 grams, require a thrust of 2030 grams of force, whereas for a total aircraft weight of 1,230 grams a thrust of 2510 grams is required, and at an aircraft weight of 1495 grams a minimum thrust of 3040 grams is required. The results also show that the thrust generated is not linear with the throttle position